Selective video encryption algorithm based on H.264/AVC and AES - Omar zakaria, Mohamed Abomhara; Khalifa, Othman Omran (IIUM Press, 2011)
H.264/AVC is an industry standard that has been designed to address different technical solutions such as broadcast applications, interactive or serial storage. conversational services, Video on Demand or multimedia streaming services [1]. The main objective behind the H.264 [2][3] development was to build a high peIformance video coding standard by adopting a back to basics approach with a simple and straightforward design using well known blocks. H.264/AVC is based on the conventional block motion compensated video coding the same way as the existing standards